Development of a TaqMan qPCR assay for detection of Alexandrium spp and application to harmful algal bloom monitoring. (April 2019) - Hatfield, Robert G.; Bean, Timothy; Turner, Andrew D.; Lees, David N.; Lowther, James; Lewis, Adam; Baker-Austin, Craig
Abstract: The Genus Alexandrium is a widespread dinoflagellate marine phytoplankton that is the primary causative organism causing Paralytic Shellfish Poisoning (PSP) intoxications in European waters. EU food safety directives specify that EU Member States must implement a routine monitoring programme to mitigate risks associated with bio-accumulation of biotoxins by bivalve shellfish, such as those produced by Alexandrium. This strategic drive comprises of both direct testing of bivalve flesh for the presence of regulated toxins and an early warning phytoplankton monitoring programme. In the UK the flesh testing moved away from animal bio-assays to analytical chemistry techniques, whereas phytoplankton monitoring methods have seen little technological advancement since implementation. Methods currently utilize light microscopy and manual enumeration of different algal species. These methods although proven are time consuming, reliant on highly trained staff, have high limits of detection (LOD) with low specificity, unable to reliably identify Alexandrium to species level. The implications of these limitations of the techniques mean that in the case of Alexandrium the LOD is also the action limit and as such it is easy to miss positive samples affecting the efficacy of any early warning strategy. This study outlines the development, preliminary method characterisation, validation and trial implementation of an alternative early warning technique, utilizing quantitative PCR to identify water samples containing Alexandrium cells. The approach outlined in this document, showed an improved correlation with flesh toxicity, improved sensitivity, improved throughput compared to traditional light microscopy methods and there was also good correlation with higher cell abundance samples when compared to the light microscopy results. The application of this approach to routine water samples was explored and was found to demonstrate potential as a corroborative method for use during flesh intoxication episodes. This study offers potential for future improvements in the accuracy and sensitivity of phytoplankton monitoring whilst ensuring continuity of public safety, providing cost savings and offering new research opportunities. Highlights: An inhouse qPCR assay was developed using the 18s rDNA to detect Alexandrium spp. qPCR had reduced LOD & improved specificity when compared to light microscopy. qPCR had a higher correlation to toxicity data when compared to light microscopy DNA extracts were found to be stable when fixed with Lugol's for >800 days.